Psychological ownership: A review and research agenda - Dawkins, S.; Tian, Amy; Newman, A.; Martin, A. (2017)
The concept of psychological ownership (PO) reflects a state in which individuals feel as though the target of ownership (e.g., job or organization) is theirs. In recent years, there has been an expansion of research linking PO with a range of desirable employee attitudes and behaviors. However, the theoretical foundations of the construct, its measurement, the factors that influence its development, and when and how it influences outcomes are areas of continued debate in the literature. In this article, we provide a narrative review of extant PO literature with the aim of developing a research agenda that encourages scholars to target opportunities for future research. In particular, we highlight the need for continued refinement of the conceptualization and measurement of PO, and development of its nomological network. In addition, we call for greater investigation of PO towards different objects or foci; examination of possible multilevel applications of PO research; identification of potential boundary conditions of PO; and exploration of the influence of culture and individual differences on the development and influence of PO. We also introduce alternative theoretical approaches for understanding and investigating PO. In doing so, we provide a roadmap for scholars to progress the development of the field.